The Role of The Islamic Development Bank (IsDB) in Socio-Economic Development in Organization of Islamic Cooperation (OIC) Countries - Syahrir Akbar (Jisiera: The Journal of Islamic Studies and International Relations, 2025)
The Islamic Development Bank (IsDB) plays a crucial role in promoting socio-economic development among Organization of Islamic Cooperation (OIC) member countries. As a Sharia-compliant multilateral financial institution, IsDB provides financing, technical assistance, and capacity-building programs to bridge economic disparities between its member states. This study analyzes the role, challenges, and opportunities of IsDB in addressing development issues through infrastructure investment, human capital development, and financial inclusion. Using a SWOT analysis approach, the study identifies internal strengths and weaknesses, as well as external opportunities and threats, that impact IsDB’s effectiveness. The findings indicate that while Islamic financing mechanisms enhance financial inclusion and economic resilience, challenges such as bureaucratic inefficiencies, reliance on member-state contributions, and diverse regulatory frameworks hinder IsDB's operational efficiency. To optimize its role, strategic policy recommendations based on the SWOT matrix are proposed, focusing on strengthening financial mechanisms, expanding partnerships, and fostering innovation. This study highlights the importance of adaptive strategies in ensuring that IsDB remains a key driver of sustainable development in OIC nations.